The utilization of outpatient rehabilitation services and quality of life in children with cerebral palsy in Hospital Universiti Sains Malaysia (HUSM) - Lim Chia, Shing (Pusat Pengajian Sains Perubatan Universiti Sains Malaysia, 2008)
Cerebral palsy (CP) is one of the major developmental disability affecting function in children. The therapy, education, and technology can help those CP children by improving functional abilities and quality of life (QOL). The general objective of the study was to determine the relationship between the utilization of outpatient rehabilitation services and quality of life (QOL) in children with cerebral palsy (CP) in HUSM. The Cerebral Palsy Quality of Life Questionnaire for Children (CP QOL-Child) Parent-proxy version has been used to assess QOL in children with CP via quantitative approach. This was a quantitative correlational study using a survey design and purposive sampling. There were 1 0 respondents in this study (n = 1 0). The mean (SD) age of the respondents in this study was 40 (5.48) years old. The median (IQR) of total hours using the rehabilitation services was 43.5 (43.3) hours. The mean (SD) score of quality of life in the study was 64.68 (7.55). From the Pearson correlation test results, there was no significant relationship between the utilization of the services (total hours) and QOL in children with CP with p = 0.316 (p > 0.05). In conclusion, quality of life was not influenced by a single factor, i.e. the utilization of the rehabilitation services.